2009
DOI: 10.2528/pier09092406
|View full text |Cite
|
Sign up to set email alerts
|

Dual Linear/Circular Polarized Plannar Antenna With Low Profile Double-Layer Polarizer of 45⺠Tilted Metallic Strips for Wimax Applications

Abstract: Abstract-A low profile double-layer polarizer structure is presented for planar patch antennas to obtain circular polarization in 3.5 GHz WiMAX band (3.4-3.6 GHz ≈ 5.7% bandwidth). Each polarizer layer is composed of 45 • tilted metallic strips on a printed circuit. A bandwidth widening is obtained due to a significant reduction of the distance between polarizer and patches. The associated effects from the interaction of the two structures have been studied. A 2 × 2 array prototype has been implemented and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…M. Euler and et al achieved minimum Axial Ratio 3dB and axial ratio bandwidth of 0.5% with -3.2 transmission loss of polarizer [14]. Masa-Campos and et al used the double-layer polarizer approach to obtain circular polarization in order to 3dB axial ratio on operational bandwidth of 5.7% [15]. G. I. Kiani and et al observed the transmission loss 6 dB with narrow band and 1.0 axial ratio through polarizer at 75 GHz [16].…”
Section: Introductionmentioning
confidence: 99%
“…M. Euler and et al achieved minimum Axial Ratio 3dB and axial ratio bandwidth of 0.5% with -3.2 transmission loss of polarizer [14]. Masa-Campos and et al used the double-layer polarizer approach to obtain circular polarization in order to 3dB axial ratio on operational bandwidth of 5.7% [15]. G. I. Kiani and et al observed the transmission loss 6 dB with narrow band and 1.0 axial ratio through polarizer at 75 GHz [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to build an instrument with hundreds of array elements, each unit needs to be small to allow for close-packing. Other kind of circular polarizers such as microstrip polarizer [17][18][19][20][21][22][23] also have the disadvantage of narrow bandwidth and low efficiency due to losses of conductor, dielectric and surface wave.…”
Section: Introductionmentioning
confidence: 99%
“…However, the design of a broadband circularly polarized patch antenna that uses a single feed has long been a challenging problem, as compared to the design of linearly polarized (LP) and the dual-fed circularly polarized (CP) patch antennas [7,8]. Especially, the single-fed single-patch CP antenna has inherently narrow impedance and axial ratio (AR) bandwidths of 1%-2% [9,10].…”
Section: Introductionmentioning
confidence: 99%